Meningkatkan Keterampilan Menulis Hasil Observasi Menggunakan Teknik Pohon Faktor Dalam Pembelajaran Bahasa Indonesia di Kelas X SMA Nu Al Fudloli Ganjaran Gondanglegi Malang Tahun Pelajaran 2018/2019 - M. Mujtaba; Yusron Yusuf (Jurnal Tinta, 2019)
Writing is one of the language skills used to communicate indirectly. Writing skills cannot come automatically without regular practice. Based on observation, writing is a difficult activity for some students. This can be seen in the learning activities of writing observations in class X of Al Fudloli NU high school which is still lacking. The use of the factor tree technique is one technique whose implementation is the same as the spider web technique. The technique is only to write the main ideas or keywords to be developed into written observations in the form of paragraphs. The application of this technique begins with dividing groups, assigning each group to make observations outside the classroom, and developing the results in the classroom. The purpose of this research are: (1) describe the results of writing observations of class X students of Al Fudloli NU High School, (2) describe the application of factor tree learning techniques in writing observations, and (3) describe student learning outcomes in writing observations using factor tree techniques in Indonesian subjects in class X of Al Fudloli NU High School. Based on the results of this class action research it can be concluded: (1) pre-cycle there are 5 students who get grades in accordance with KKM and 15 students get grades below KKM or only 25% are in accordance with KKM and 75% who are under KKM, (2) the application of the factor tree technique that is by looking for the main ideas first then finding derivatives or sub-subjects that are in the shade of the main ideas, then developing the main ideas and sub-topics into sentences and combining them into paragraphs, (3) The results in the first cycle increased in value from 20 students 12 students got grades in accordance with KKM and 8 students were still below KKM. Thus it can be concluded that the writing skills of the results of initial observations of class X students have increased by 35%, initially only 25% of students who were in accordance with KKM. In the first cycle there are 60% of students who are in accordance with KKM, with an average grade of 69.5. The results of the second cycle increased in value from 20 students to 20 students got grades in accordance with KKM. Thus it can be concluded that writing skills from the observations of class X students have increased by 40%, initially only 60% of students were in accordance with KKM on the first cycle, and there were 100% of students who were in accordance with KKM in the second cycle with an average grade 84.25. Thus the application of the factor tree technique can improve writing skills of students' observations.